A JOURNAL OF THE PLAGUE YEAR (REVISITED CLASSICS) - Defoe, Daniel (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2008)
If we inquire further into the secret of Defoe's success in the "History of the Plague," we shall find that it consists largely in his vision, or power of seeing clearly and accurately what he describes, before he attempts to put this description on paper. As Defoe was but four years old at the time of the Great Plague, his personal recollection of its effects must have been of the dimmest; but during the years of childhood (the most imaginative of life) he must often have conversed with persons who had been through the plague, possibly with those who had recovered from it themselves. He must often have visited localities ravaged by the plague, and spared by the Great Fire of 1666; he must often have gazed in childish horror at those awful mounds beneath which hundreds of human bodies lay huddled together,—rich and poor, high and low, scoundrel and saint,—sharing one common bed at last. His retentive memory must have stored away at least the outline of those hideous images, so effectively recombined many years later by means of his powerful though limited imagination.